An increase in investment and development aid China's for Cambodia in the second decade of the 21st Century - Hung, Vo Minh; Tuan, Nguyen Khoa (Edelweiss Applied Science and Technology, 2025)
The article analyzes the China-Cambodia relationship in the period 2010 - 2021 in the economic field, thereby considering the nature of this relationship and the achieved results, limitations, and challenges of the bilateral relationship. Through the analysis and synthesis of relevant data and documents, official statements of the countries' governments, and scholarly studies on China-Cambodia economic relations, an objective assessment of the relationship between the two countries is made. It can be seen that the financial relationship between China and Cambodia is one with a long history and many ups and downs. However, the essential thing throughout the process of this relationship is that the interests of both sides are still prioritized. Nevertheless, the China-Cambodia relationship is generally very close, with few fluctuations or conflicts of interest. The article concludes that Cambodia-China relations have developed rapidly in many aspects over the past decade, especially in the economic field. In particular, China's development in relations with Cambodia is considered a successful model of the comprehensive strategic partnership and friendly neighborly partnership. In other words, the Cambodian relationship aligns with the wishes of both Cambodia and China, reflecting the expectations and perceptions of both sides about a comprehensive and reliable strategic partnership within this cooperation framework. However, Cambodia-China relations, especially from the Cambodian side, are and will continue to face many challenges in all aspects, from politics, diplomacy, defense, and security to economy and society.